2015
DOI: 10.3945/jn.114.205336
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Patterns Methods Project: Synthesis of Findings across Cohorts and Relevance to Dietary Guidance

Abstract: The Dietary Patterns Methods Project (DPMP) was initiated in 2012 to strengthen research evidence on dietary indices, dietary patterns, and health for upcoming revisions of the Dietary Guidelines for Americans, given that the lack of consistent methodology has impeded development of consistent and reliable conclusions. DPMP investigators developed research questions and a standardized approach to index-based dietary analysis. This article presents a synthesis of findings across the cohorts. Standardized analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
232
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(252 citation statements)
references
References 46 publications
(98 reference statements)
11
232
0
9
Order By: Relevance
“…It provided a systematic comparison of 4 key diet quality indices across multiple cohorts, using standardized measures, to examine their associations with mortality. 12 Results indicated that higher diet quality was significantly and consistently associated with reduced risk of death attributable to all causes, cardiovascular disease, and cancer in comparison with lower diet quality, independent of known confounders.…”
Section: Investigator-definedmentioning
confidence: 87%
“…It provided a systematic comparison of 4 key diet quality indices across multiple cohorts, using standardized measures, to examine their associations with mortality. 12 Results indicated that higher diet quality was significantly and consistently associated with reduced risk of death attributable to all causes, cardiovascular disease, and cancer in comparison with lower diet quality, independent of known confounders.…”
Section: Investigator-definedmentioning
confidence: 87%
“…Tener una dieta de calidad se asocia significativa y consistentemente con un riesgo de muerte por las causas antes citadas un 11-28% menor (137).…”
Section: Patrones Dietéticosunclassified
“…In rural SSA, the proportion of adult deaths due to non-communicable diseases has increased: from 16 % in 2003 to 24 % in 2007 in Tanzania (5) and from 35 % in 2003 to 45 % in 2010 in Kenya (6) . One of the potentially modifiable risk factors for noncommunicable diseases is diet, which is well documented to affect the risk for many cardiometabolic diseases and cancers (7)(8)(9)(10) . In SSA, although data remain sparse, it is clear that access to food is increasing but diet quality is worsening.…”
mentioning
confidence: 99%